Development of a Technique for Energy Storage Using a Piezoelectric Generator for Low-Power Consumption Devices Supporting Stand-Alone Wireless Sensors for Smart Systems - Thainiramit, Panu (International Journal of Integrated Engineering, 2019)
In the last decade, microcontrollers (MCU) have become part of daily life. MCU can function as stand-alone devices to control automatic machines in so-called Smart Embedded Systems (SEMs) which can operate independently using Direct Current (DC) power. Such systems actually need a conventional battery to function and battery lifetime is a major problem since it is not easy to monitor when exhausting the power. This research can solve the problem, how to keep the SEM continually functioning by using piezoelectric power generator to charge the rechargeable battery through the enhancement circuit technique. This is described by the piezo-current and piezo-voltage transferred into a small rechargeable battery. The piezo-power is generated under the constant vibration based on ambient-source movement. The rechargeable battery, capacity 150 mAh, can be fully charged within 40 hours. Moreover, this paper presents the theoretical and experiment results from the output power of the piezo-generator. The results confirm that DC-DC converter technique can validate the model representation and achieve the power enhancement of piezoelectric generator.